Perlindungan Hukum Dan Pelestarian Tradisi Siat Yeh Banjar Teba Desa Adat Jimbaran - Dwijanata, Anak Agung Bagus Cahya; Pramana, I Gede Pasek (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 2 (2023)DO - 10.24843/JMHU.2023.v12.i02.p14, 2023)
The purpose of this study was to identify and analyze the authority of the Jimbaran Traditional Village regarding efforts to protect the law and preserve the Siat Yeh tradition and efforts to protect the law and preserve the Siat Yeh tradition carried out by the Jimbaran Traditional Village. The type of research used in this article is empirical legal research which is carried out by examining the facts that occur in a problem. As well as using interviews as the main data. Based on the results of the research, the following conclusions can be formulated: Jimbaran Traditional Village has authority in legal protection and tradition preservation based on the provisions of the 1945 Constitution, the Culture Promotion Law, and the Regional Regulations on Traditional Villages in Bali; and With the authority that belongs to the Jimbaran Traditional Village to protect the law and preserve the Siat Yeh tradition in the form of making pararem banjars, taking an inventory of traditions through the cultural service, and invalidating them in inscriptions. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis kewenangan Desa Adat Jimbaran terkait upaya perlindungan hukum dan pelestarian tradisi siat yeh dan upaya perlindungan hukum dan pelestarian tradisi siat yeh yang dilaksanakan oleh Desa Adat Jimbaran. Jenis penelitian yang digunakan dalam artikel ini adalah penelitian hukum empiris yang dilakukan dengan mengkaji suatu fakta-fakta yang terjadi dalam suatu masalah. Serta menggunakan wawancara sebagai data utama. Berdasarkan hasil penelitian, dapat dirumuskan kesimpulan sebagai berikut : Desa Adat Jimbaran memiliki kewenangan dalam perlindungan hukum dan pelestarian tradisi berdasarkan ketentuan UUD 1945, UU Pemajuan Kebudayaan, dan Perda Desa Adat di Bali; dan Dengan kewenangan yang dimiliki Desa Adat Jimbaran melakukan perlindungan hukum dan pelestarian tradisi siat yeh dalam bentuk membuat pararem banjar, menginventaris tradisi melalui dinas kebudayaan, dan mencacatkan dalam prasasti.